2018
DOI: 10.1111/php.12883
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Comparative Susceptibility of Microbial Species to Photoinactivation Using 380–480 nm Violet‐Blue Light

Abstract: Antimicrobial violet-blue light is an emerging technology designed for enhanced clinical decontamination and treatment applications, due to its safety, efficacy and ease of use. This systematized review was designed to compile the current knowledge on the antimicrobial efficacy of 380-480 nm light on a range of health care and food-related pathogens including vegetative bacteria, bacterial endospores, fungi and viruses. Data were compiled from 79 studies, with the majority focussing on wavelengths in the regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 110 publications
4
53
0
Order By: Relevance
“…Inactivation was claimed by Halstead et al as well, who investigated 400 nm light against 34 isolates and found violet light effective against P. aeruginosa and S. aureus [53]. Based on these findings and the literature, there is no doubt about the antibacterial activity of the violet light [32,40,41,43,49,51,54,56,[63][64][65][66][67]. However, the evaluation of its effectiveness and a direct comparison of the results, obtained by different studies, are more complicated.…”
Section: Violet Lightmentioning
confidence: 93%
See 2 more Smart Citations
“…Inactivation was claimed by Halstead et al as well, who investigated 400 nm light against 34 isolates and found violet light effective against P. aeruginosa and S. aureus [53]. Based on these findings and the literature, there is no doubt about the antibacterial activity of the violet light [32,40,41,43,49,51,54,56,[63][64][65][66][67]. However, the evaluation of its effectiveness and a direct comparison of the results, obtained by different studies, are more complicated.…”
Section: Violet Lightmentioning
confidence: 93%
“…In some works, blue light (420-470 nm) has been tested as well, showing a strong effect against both Gram-positive (Bacillus cereus, Listeria monocytogenes and methicillin-resistant S. aureus) and Gram-negative pathogens (P. aeruginosa, Salmonella Typhimurium and E. coli) in their planktonic form [39][40][41]49,50,54,56,[65][66][67][68]. However, Abana et al claimed that the effect of 455 nm is not completely bactericidal on E. coli but depends on the microorganism (pathogenic or non-pathogenic) and growth phase.…”
Section: Blue Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…An in vitro study evaluating the efficacy of violet 405nm light in treating ampicillin resistant Escherichia coli found an 81.7% reduction of bacterial growth with irradiance of 2.89 mW/cm 2 over 120 min (p < 0.001) [56]. Similarly, a review of both Gram-positive and Gram-negative bacteria susceptibility to violet light therapy between 380 and 480 nm found a 91% inactivation of Pseudomonas aeruginosa with 405 nm of VLT [57]. Finally, heat has been shown to be effective in disrupting the microbial membrane and therefore killing bacteria.…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%
“…Photodynamic inactivation of vegetative bacteria and spores by high-intensity visible light within the blue range of the spectrum at wavelengths of ϳ400 nm has recently garnered significant interest due to the intrinsic antimicrobial characteristics of blue light (17)(18)(19). Significant activity has been demonstrated against Bacillus and Clostridium species; however, spores require a significantly larger dose of blue light to mediate killing than do vegetative cells (20).…”
mentioning
confidence: 99%